The selective cognitive benefits of long-term Tai Chi practice on executive function of students: a study on young adults - Darrin, Sime Nkemeni; Hao, Hong; Long, Cheng; Duangchit, Chanthavone; Fangfang, Xu; Tiegang, Zhang (Frontiers in Psychology, 2026)
IntroductionThis study investigates the cognitive effects of long term (years of practice) Tai Chi practice, revealing mixed outcomes for executive functions. This study equally addresses the gap in research regarding the long term effects of Tai Chi, emphasizing its influence on the executive functions of young adults.MethodsUsing the BRIEFA scale and tasks like the Flanker task, More Odd Shift Task, and Nback tasks, significant differences emerged between Tai Chi students and nonstudents.ResultsIn the results, Tai Chi students demonstrated superior inhibitory control and working memory compared to non Tai Chi students, as illustrated by BRIEFA results and performance on the back task. However, no significant difference in cognitive flexibility was found, possibly due to automatic reflexes from repetitive routines. This lack of cognitive flexibility improvement may stem from practitioners' instinctive responses to familiar movements, restricting adaptive strategy shifts. The results obtain illustrates that long term Tai Chi practice selectively enhances specific cognitive domains, notably inhibition and working memory, while leaving cognitive flexibility unchanged.DiscussionThese benefits are attributed to Tai Chi's combination of physical movement, cognitive engagement, and mindfulness through rhythmic breathing, which enhances mental clarity, attentional discipline, and distraction management. This result challenges the assumption that Tai Chi uniformly enhance the cognitive function, highlighting the need for further research into its long term effects on specific cognitive domains. By elucidating these selective enhancements, future studies can explore the mechanisms underlying these outcomes and their implications for cognitive health. Such research could inform interventions aimed at optimizing Tai Chi practices to maximize cognitive benefits across diverse populations.